Differentiated modulation of signaling molecules AMPK and SIRT1 in experimentally drug-induced hepatocyte injury - Njeka Wojnarova, Lea; Kutinová-Canová, Nikolína; Arora, Mahak; Farghali, Hassan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2023)
AIM: Currently available medicines have little to offer in terms of supporting the regeneration of injured hepatic cells. Previous experimental studies have shown that resveratrol and metformin, less specific activators of AMP-activated protein kinase (AMPK) and sirtuin 1 (SIRT1), can effectively attenuate acute liver injury. The aim of this experimental study was to elucidate whether modulation of AMPK and SIRT1 activity can modify drug/paracetamol (APAP)-induced hepatocyte damage in vitro. METHODS: Primary rat hepatocytes were pretreated with mutual combinations of specific synthetic activators and inhibitors of SIRT1 and AMPK and followed by a toxic dose of APAP. At the end of cultivation, medium samples were collected for biochemical analysis of alanine-aminotransferase and nitrite levels. Hepatocyte viability, thiobarbituric reactive substances, SIRT1 and AMPK activity and protein expression were also assessed. RESULTS: The harmful effect of APAP was associated with decreased AMPK and SIRT1 activity and protein expression alongside enhanced oxidative stress in hepatocytes. The addition of AMPK activator (AICAR) or SIRT1 activator (CAY10591) significantly attenuated the deleterious effects of AMPK inhibitor (Compound C) on the hepatotoxicity of APAP. Furthermore, CAY10591 but not AICAR markedly decreased the deleterious effect of APAP in combination with SIRT1 inhibitor (EX-527). CONCLUSION: Our findings demonstrate that decreased AMPK activity is associated with the hepatotoxic effect of APAP which can be significantly attenuated by the administration of a SIRT1 activator. These findings suggest that differentiated modulation of AMPK and SIRT1 activity could therefore provide an interesting and novel therapeutic opportunity in the future to combat hepatocyte injury.
Keywords: hepatocyty; AMP-Activated Protein Kinases; Sirtuin 1; Hepatocytes; krysa rodu Rattus; sirtuin 1; Cyclopentanes; Animals; cyklopentany; paracetamol; Acetaminophen; proteinkinasy aktivované AMP; lékové postižení jater; Chemical and Drug Induced Liver Injury; zvířata; Rats